Ética, direitos humanos e pesquisa biotecnológica: Uma abordagem complexa nos espaços amazônicos - Queiroz, Lincoln Alencar de (2008)
Genetics begins at Mendel’s garden, however it’s knowledge changes as it is overtaken by the biopower of a totalitarian government, and nowadays has its seeds planted onto the garden of consumerism. Science is not axiomatically neutral as it is incorporated in the productive process of capitalism. As the market takes it, science follows its rules that are the same in everywhere. As it is applied on human beings science also takes its research object through the patenting rights and looks straight to make profits in order to have back the initial investments made. In the field of law studies it is noticed a paradox between the theory that denies disposition of the body and the possibility of patenting living beings. The new knowledge brought by science does affect everyone’s life and for this reason the defense of dignity begins by the defense of a public and democratic space. The use of human genetics aiming high to obtain profits is incompatible with human dignity and, it is indeed an indignity because it forces men from away from its history and culture. The Yanomamö, the Suruí, and the Karitiana were victims of such an indignity as they were enforced to take part in researches that they did not allowed, and also beneficiate only the power and the prestige of the researchers themselves. Science does have power and also have great influence in everyone lives, and, for this reason, it holds the responsibility to do what is good for men. The sense of goodness is decided inside men’s culture and the community. The Human Rights are the ethical and juridical foundations upon which the concept of human dignity is built and also the very basis of the critic of the traditional civil law which ca only see the human as a proprietary and thus does not offer protection against the commoditization. Key-words: Science. Genetics. Market. Patents. Human dignity. Human rights. Commoditization.